Business Statistics: for contemporary decision making - Black, Ken (Wiley, 2025)
Business Statistics uses current real-world data to equip students with the business analytics techniques and quantitative decision-making skills required to make more thoughtful, information-based decisions in today's workplace. Helping the student understand business analytics and the role that business statistics plays in it, the book has infused the language of business analytics along with its definitions, approaches, and explanations throughout the text. Continuing the tradition of presenting and explaining business statistics using clear, complete, and student-friendly pedagogy, this Indian edition includes new chapter cases reinforcing the vibrancy and relevance of statistics. In addition, topical changes have been made in select chapters and problems have been revised in all the chapters.